Asas Pembuktian Terbalik dalam Penyelesaian Kasus Kejahatan Korupsi - Muhammad Abdul Kholiq (Fakultas Hukum Universitas Islam Indonesia, 2002)
Universally, corruption have been comprehended as aextremely serious crime and it has multidimensional impact sothat it caused the state social life becomes abnormal because of the 'senous' corruptive level. Therefore, it needs to be handled braverly In applying various kinds ofstrategy both for the common cases and 'abnormal'ones. One of abnomal strategy in the frame of coping with: the crime of corruption depicted above Is the need ofreverse authentication principle In order to make easy in solving the process of case solution and accelerate the effort ofrescuing on the state financial and economy. In the theory perspective, although the idea of application on reverse authentication principle has justificative principles and it produces confrontative problems with the various principleselse which Is established in the doctrine ofthe material criminal law as well as formal one recently. By this writing, it may be seen as the effort to describe the problem as well as the urgency of idea on reverse authentication principle and then it tries to offer solution about howis the better way ofthe idea responded in the policy ofcoping with the corruption for the future.